Association between distress and displacement settings: a cross-sectional survey among displaced Yazidis in northern Iraq - Phuong N. Pham; Laila Fozouni; Abdulrazzaq al-Saiedi; Kevin Coughlin; Patrick Vinck (BMC, 2021)
Abstract Background Globally 70.8 million people have been forcibly displaced from their homes and are at disproportionally high risk for trauma. At the time of this study, there was an estimated 1.6 million internally displaced persons (IDP) in Iraq, more than two-thirds of whom reside in private, urban settings. This study aims to understand the impact of post-displacement accommodation on mental well-being of the Yazidi minority group displaced in Iraq. Methods Multi-stage stratified sampling was used to randomly select IDPs in camp and out of camp settlements in northern Iraq. Standardized questionnaires evaluated factors including exposure to violence and self-reported distress symptoms (measured by Impact of Event Scale-Revised). A multi-variate linear model assessed the relationship between settlement setting and distress symptoms. Results One thousand two hundred fifty-six displaced Yazidi participants were included in the study: 63% in camps and 37% out of camps. After controlling for exposure to violence, social cohesion, unemployment, and access to basic services, IDPs in camps were predicted to have a 19% higher mean distress symptom score compared to those out of camps. Conclusions This study provides a framework to investigate post-displacement accommodation as a potential intervention to improve well-being for displaced populations. With a shift towards new models of emergency and long-term housing, it is important to understand the potential and limitations of more decentralized models, and identify effective methods to maintain access to basic services while improving living conditions for both displaced populations and their host communities.